Actividad hipoglicemiante del extracto hidroalcohólico de Portulaca oleraceae L. en ratas con hiperglicemia inducida por aloxano - Carrión Pacaya, Katherin (2025)
Diabetes mellitus is a disease that represents a global public health problem, with a high prevalence in Peru. Given the limitations and adverse effects of conventional treatments, there is an interest in the use of medicinal plants as a therapeutic alternative. This study evaluated the hypoglycemic effect of hydroalcoholic extract from the whole plant of Portulaca oleraceae L. (purslane). Diabetes was induced in rats by administering aloxane (135 mg/kg), 4 groups were formed (n=06 per group): a white control group, a negative control group, two hyperglycemia groups treated orally with hydroalcoholic extract of P. oleraceae L. at doses of 250 mg/kg and 500 mg/kg, respectively, a semi-automated biochemical analyzer (ThermoBio Neo-smart) was used to measure blood glucose in the experimental groups at different times (1, 3, 6 and 24) after oral administration of extract . The two groups of hyperglicemia rats treated with the extract showed a significant reduction in blood glucose levels (p≤0.05) compared to the negative control group, with decreases of 63% (500 mg/kg) and 60.9% (250 mg/kg). Phytochemical screening was carried out where alkaloids, triterpenes, steroids, carotenes, saponins, phenols and tannins, amino acids and amines were identified. These results suggest that the hydroalcoholic extract of P. oleraceae L. has a significant hypoglycemic effect. These preliminary findings support the potential of P. oleraceae L. as a promising alternative in diabetes management.